P-119 Antibiotic stewardship in a hospice environment: an audit of start smart then focus. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Matthews, Annelise; Kirupanadan, Aharani; O'Dea, Roisin; Duttagupta, Tina; Ferguson, James; Kayani, Sumera
Abstract : Background: Antimicrobial stewardship is an important element of improving the safety and quality of patient care and reducing the emergence and spread of antimicrobial resistance. The Start Smart then Focus Toolkit was introduced to help NHS Trusts improve antibiotic stewardship (Public Health England, 2018). Previous work has shown hospice patients are at high risk of infections due to frailty and immunocompromise. Furthermore there may be poor documentation of antibiotic prescribing (Donald & Lindsay, 2014). Aims: To promote antibiotic stewardship by changing prescribing practice and introducing a sticker for antibiotic prescriptions. Methods: Two matched retrospective audits of hospice inpatients over one-month periods in July 2017 and February 2018. Notes were analysed for patients prescribed antibiotics and drug charts checked for review dates, stop dates, indications and signatures (Public Health England, 2018). The February 2018 notes were also checked to see if antibiotic stickers were used on the drug charts. Results: In February 2018, of the 30 inpatients, 16 were prescribed antibiotics, compared to 12 of 38 in July 2017. The original audit showed poor compliance with standards, with 50% (6/12) review dates, 75% (9/12) stop dates and 41% (5/12) indications. Correct prescribing increased with sticker use, with 100% (4/4) review dates, 50% (2/4) stop dates and 100% (4/4) indications compared to 17% (2/12) review dates, 0% (0/12) stop dates, and 75% (9/12) indications in the February 2018 re-audit. However, there was poor sticker use with only four of 16 prescriptions on stickers. Conclusions: The stickers were an effective intervention for improving antibiotic stewardship, but one dependent on individual prescribers remembering to use them. In a hospice with continually changing junior staff, the best option may be to change the drug chart to have an antibiotic page to meet the Start Smart then Focus criteria. Further auditing could examine whether the hospice completes the Toolkit's Secondary Care Prescriber's Checklist (Public Health England, 2018).